Extraction of the GPR instantaneous centroid frequency based on the envelope derivative operator and ICEEMDAN - Zhang, Xuebing; Hu, Xin; Qiu, Zheli; Feng, Xuan; Qin, Yuxiang (Remote sensing letters, 2023)
The instantaneous centroid frequency attribute describes how the main frequency changes with the ground-penetrating radar (GPR) signal propagating in the subsurface medium. In this letter, we present a new approach for extracting the instantaneous centroid frequency based on the improved complete ensemble empirical mode decomposition with adaptive noise (ICEEMDAN) and the envelope derivative operator (EDO). The ICEEMDAN decomposition is fully adaptive, and the instantaneous frequency and the instantaneous energy can be tracked with non-negativity by using the EDO algorithm. To verify the effect of the proposed scheme, we have applied it to a GPR forward model and field data, and made comparisons with the instantaneous centroid frequency schemes shown in the previous literature. It can be observed that the proposed scheme in this letter is less subject to noise interference and can localize subsurface interfaces and anomaly bodies with higher resolution. The proposed scheme can be used as an effective complement to GPR signal processing and interpretation.